The human genome as the common heritage of humanity - Kabata, Faith; Thaldar, Donrich (Frontiers in Genetics, 2023)
While debate on international regulation of human genomic research remains unsettled, the Universal Declaration on the Human Genome and Human Rights, 1997 qualifies the human genome as "heritage of humankind" in a symbolic sense. The article assess whether, how and to what extent the common heritage framework is relevant in regulation of human genomic research. Using document analysis, it traces the history of the Human Genome Project to reveal the international scientific community's race against privatization of the human genome that resulted in qualification of the human genome as common heritage of humanity. Further, it reviews the archival records of UNESCO's International Bioethics Committee to discover the rationale for qualifying the human genome as common heritage of humankind. The article demonstrates the continued relevance of the application of the common heritage of mankind framework at the collective level of the human genome, but finds that the framework is at odds with the individual dimension of the human genome, based on individual personality rights. The article argues that the right to benefit from scientific progress and its applications offers an alternative international regulatory framework for human genomic research.